2017
DOI: 10.5194/acp-17-911-2017
|View full text |Cite
|
Sign up to set email alerts
|

Short-period mesospheric gravity waves and their sources at the South Pole

Abstract: Abstract. The sourcing locations and mechanisms for shortperiod, upward-propagating gravity waves at high polar latitudes remain largely unknown. Using all-sky imager data from the Amundsen-Scott South Pole Station, we determine the spatial and temporal characteristics of 94 observed smallscale waves in 3 austral winter months in 2003 and 2004. These data, together with background atmospheres from synoptic and/or climatological empirical models, are used to model gravity wave propagation from the polar mesosph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…However, low LTAs over Antarctica have also been seen by Mehta et al. (2017), with higher phase speed measurements originating near the surface around the south pole. Preusse et al.…”
Section: Resultssupporting
confidence: 55%
“…However, low LTAs over Antarctica have also been seen by Mehta et al. (2017), with higher phase speed measurements originating near the surface around the south pole. Preusse et al.…”
Section: Resultssupporting
confidence: 55%
“…Gavrilov et al (1996) reported that up to 50 % of the detected waves propagate downwards in the altitude range 70 to 80 km. In the troposphere and lower stratosphere (below 20 km) Sato (1994) reported less than 10 % downwardpropagating GWs, and Mihalikova et al (2016) reported 18.4 % during wintertime and 10.7 % during summertime. From rocket observations of zonal and meridional wind components with a vertical resolution of 1 km in the altitude range 30 to 60 km, Hirota and Niki (1985) found, in middle and high latitudes, about 20 % downward-propagating GWs and 30 %-40 % in low latitudes at Northern Hemisphere stations.…”
Section: Resultsmentioning
confidence: 99%
“…The waves that were traced all the way down to the troposphere (204 waves) have intrinsic periods greater than 6.5 min, horizontal wavelengths greater than 20 km, and propagation directions predominantly southward; show a very pronounced concentration of wave initiation to the northwest at approximately 100-300 km from the observing point; and occurred consistently throughout all seasons. One possibility for the origin of these waves is the interaction of planetary waves with the background wind fields, as discussed recently by Mehta et al (2017) for the case of short-period mesospheric GWs detected at the South Pole. A detailed investigation of this hypothesis for the waves reported here is beyond the scope of this work.…”
Section: Discussionmentioning
confidence: 98%